2021
DOI: 10.1002/jgm.3318
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNAs: Promising new targets in pulmonary fibrosis

Abstract: Pulmonary fibrosis is characterized by progressive and irreversible scarring in the lungs with poor prognosis and treatment. It is caused by various factors, including environmental and occupational exposures, and some rheumatic immune diseases. Even the rapid global spread of the COVID‐19 pandemic can also cause pulmonary fibrosis with a high probability. Functions attributed to long non‐coding RNAs (lncRNAs) make them highly attractive diagnostic and therapeutic targets in fibroproliferative diseases. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 109 publications
(214 reference statements)
0
13
0
Order By: Relevance
“…Long non-coding RNAs (LncRNAs), as regulators of a variety of biological processes, have been shown to be involved in the pathophysiology of IPF, including fibroblast activation [ 7 ]. Our previous study suggested that lncRNA PFAR, identified with the mouse fibrosis arrays, promotes fibroblast differentiation during pulmonary fibrosis by sponging miR-138 to regulate the YAP1-Twist axis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (LncRNAs), as regulators of a variety of biological processes, have been shown to be involved in the pathophysiology of IPF, including fibroblast activation [ 7 ]. Our previous study suggested that lncRNA PFAR, identified with the mouse fibrosis arrays, promotes fibroblast differentiation during pulmonary fibrosis by sponging miR-138 to regulate the YAP1-Twist axis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of miRNA is also regulated by epigenetic factors, such as DNA methylation, lncRNA, cir-cRNA, and histone modification [22,[53][54][55][56][57][58][59]. Many miRNAs are also regulated in posttranscriptional processing; for example, miRNAs are spliced by argonaute (AGO) proteins [60], Drosha [61,62], Dicer [63], silencing regulatory protein KRSP [64], and tristetraprolin (TTP) [64]. The stability of miRNA is another factor that affects its expression level.…”
Section: Ncrnamentioning
confidence: 99%
“… 127 Compared with conventional protein probes, lncRNAs are the preferred potential targets because they are smaller molecules and are more diverse than proteins. 128 Hence, the designed fluorescent probe can be synthesized readily, penetrate cells efficiently, and be used for in vivo imaging of OSF. Autofluorescence spectroscopy takes advantage of the fact that different diseased tissues have unique tissue morphologic characteristics.…”
Section: Future Expectationsmentioning
confidence: 99%